Atmospheric Mercury - Robert W. Talbot (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Mercury is a serious environmental toxin that is distributed globally by large-scale atmospheric circulations. The chapters in this book cover measurements of speciated atmospheric mercury, regional modeling, continental-scale distributions across the U.S. and Canada, large-scale distributions in the free troposphere, and changes in wet deposition across the U.S. The diverse topics give snap-shots of current research areas in atmospheric mercury and some insight into policy issues in Europe. Together, the work demonstrates the complexity of atmospheric mercury and provides aspects on measuring and modeling it. Much work is needed in the future to unravel the chemical forms of oxidized atmospheric mercury and how it is intertwined in global cycling of mercury. The complexities of this work are extremely challenging for emerging atmospheric chemists.